THE EFFECTIVENESS OF COGNITIVE LEARNING STRATEGIES IN IMPROVING STUDENTS’ READING ABILITY AT THE FIRST SEMESTER STUDENTS OF ENGLISH DEPARTMENT OF KALIMANTAN ISLAMIC UNIVERSITY BANJARMASIN IN THE ACADEMIC YEAR 2014/2015 - Hidayatullah Hidayatullah; Angga Taufan Dayu (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2017)
Students are expected to have good comprehension to deal with all reading aspects and difficulties in academic context. Furthermore, as the teacher we should prepare students with learning strategies so that the students can used their learning strategies to improve their reading comprehension which could not be taught optimally in the class. The comprehension process draw on many cognitive and linguistic abilities, especially vocabulary, recalling background knowledge, sentence processing, verbal reasoning, and working memory. Therefore, reading comprehension is an area where cognitive strategies are important. The objectives of this research are to find out the effect of cognitive learning strategies in teaching reading in improving students reading comprehension, and reading difficulties faced by students.This research applied quasi-experimental design by using non-equivalent control group design pre test and post test. The experimental class is students of morning class and the controlled class is students of night class, each class consists of 35 students. Both experimental and controlled classes are given pretest and post test. However, the treatment was only given to the experimental class. The data are collected through pretest, post test and questionnaire and were analyzed by using SPSS 17.0.The research results are: 1. The cognitive learning strategies are effective in improving reading comprehension; 2. The cognitive learning strategies help students to improve their reading comprehension by themselves both inside and outside the classroom, with or without the teacher assistance; 3. the cognitive learning strategies provide students with interesting, challenging, and enjoyable classroom activity. It also contributes to help students to comprehend the material more easily.Keywords: Effectiveness, Cognitive learning strategies, Students’ reading ability